Visitor experience design - Scott, Noel, 1958-; Gao, Jun; Ma, Jianyu (CABI series in tourism management research ;, 2017)
The aim of this book is to examine the best practice in creating and delivering exciting and memorable visitor experiences from a cognitive psychological perspective. It consists of 17 chapters organized into six parts. Part I provides the theories and frameworks of the tourist experience. The next three parts examine the pre-experience stage (Part II), on-site experiences (Part III), and post-experience outcomes (Part IV). Part V provides cases of specific tourism experiences; while the lone chapter in Part VI provides a conclusion and thoughts on future research.